2021
DOI: 10.1186/s42155-021-00213-x
|View full text |Cite
|
Sign up to set email alerts
|

Splenic vein stenting for recurrent chylous ascites in sinistral portal hypertension: a case report

Abstract: Background Sinistral portal hypertension results from obstruction or stenosis of the splenic vein and is characterized by normal portal vein pressures and liver function tests. Gastrointestinal bleeding is the most common presentation and indication for treatment. Although sinistral portal hypertension-related chylous ascites is rare, several cases have described successful treatment with portal venous, rather than splenic venous, recanalization. Splenectomy is effective in the treatment of sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…There are currently literature reports on the successful treatment of LSPH bleeding with splenic vein plasty. [3][4][5] Compared with traditional splenectomy, splenic venoplasty has no surgical complications such as bleeding and infection, and has a shorter hospital stay and relatively lower overall treatment costs. [6] And compared to partial splenic embolization, splenic venoplasty has significant advantages in preventing PSPH rebleeding.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently literature reports on the successful treatment of LSPH bleeding with splenic vein plasty. [3][4][5] Compared with traditional splenectomy, splenic venoplasty has no surgical complications such as bleeding and infection, and has a shorter hospital stay and relatively lower overall treatment costs. [6] And compared to partial splenic embolization, splenic venoplasty has significant advantages in preventing PSPH rebleeding.…”
Section: Discussionmentioning
confidence: 99%
“… 14 SAE can be used as a primary intervention for SPH or an adjunct to splenectomy to lower intra-operative blood loss and rates of conversion to open surgery. 16 , 17 A lack of local expertise and high incidence of postembolization syndrome limits the wide adoption of SAE in clinical practice. 14 Postembolization syndrome presents as nausea, vomiting, or abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Splenic vein stenting has the lowest rate of rebleeding and visceral complications when compared to splenectomy and preoperative SAE. 14 , 17 , 18 Covello et al 17 reported an interesting case of SPH-associated refractory chylous ascites that was successfully treated with transhepatic splenic stenting. Even though SVS has a 92% stent patency rates at 12 months, there are still no standardized guidelines for postprocedural anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations